Epi-illumination SPIM for Volumetric Imaging with High Spatial-temporal Resolution - Yang, Bin (Nat Methods, 2019)
We designed an epi-illumination SPIM system which utilizes a single objective and has an identical sample interface as an inverted fluorescence microscope with no additional reflection elements. It achieves subcellular resolution and single-molecule sensitivity and is compatible with common biological sample holders, including multi-well plates. We demonstrated multicolor fast volumetric imaging, single-molecule localization microscopy, parallel imaging of sixteen cell lines and parallel recording of cellular responses to perturbations.